Primer-dependent synthesis by poliovirus RNA-dependent RNA polymerase (3D(pol)) - Rodriguez-Wells, Virgen (Oxford University Press, 2001)
Properties of poliovirus RNA-dependent RNA polymerase (3D(pol)) including optimal conditions for primer extension, processivity and the rate of dissociation from primer-template (k(off)) were examined in the presence and absence of viral protein 3AB. Primer-dependent polymerization was examined on templates of 407 or 1499 nt primed such that fully extended products would be 296 or 1388 nt, respectively. Maximal primer extension was achieved with low rNTP concentrations (50–100 µM) using pH 7 and low (<1 mM) MgCl(2) and KCl (<20 mM) concentrations. However, high activity (about half maximal) was also observed with 500 µM rNTPs providing that higher MgCl(2) levels (3–5 mM) were used. The enhancement observed with the former conditions appeared to result from a large increase in the initial level or active enzyme that associated with the primer. 3AB increased the number of extended primers at all conditions with no apparent change in processivity. The k(off) values for the polymerase bound to primer-template were 0.011 ± 0.005 and 0.037 ± 0.006 min(–1) (average of four or more experiments ± SD) in the presence or absence of 3AB, respectively. The decrease in the presence of 3AB suggested an enhancement of polymerase binding or stability. However, binding was tight even without 3AB, consistent with the highly processive (at least several hundred nucleotides) nature of 3D(pol). The results support a mechanism whereby 3AB enhances the ability of 3D(pol) to form a productive complex with the primer-template. Once formed, this complex is very stable resulting in highly processive synthesis.